2016
DOI: 10.1016/j.ijfoodmicro.2016.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Impact of inhibitory peptides released by Saccharomyces cerevisiae BDX on the malolactic fermentation performed by Oenococcus oeni Vitilactic F

Abstract: A previous study has shown that the malolactic fermentation (MLF) was inhibited during sequential fermentations performed with the pair Saccharomyces cerevisiae BDX/Oenococcus oeni Vitilactic F in synthetic grape juices. A yeast peptidic fraction with an apparent MW of 5-10kDa was involved in the inhibition. In the present study, the MLF was also inhibited in Cabernet Sauvignon and Syrah wines. The inhibition due to the peptidic fraction was maintained despite high phenolic contents. Kinetic studies showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…Since MLF is one of the main energy sources during winemaking, the inhibition of the bacterial growth can be a consequence of the MLF inhibition. Rizk et al (2016) also showed that the same pairing (S. cerevisiae Uvaferm BDX/O. oeni Vitilactic F) maintained the MLF inhibition in Cabernet Sauvignon and Syrah wines.…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations
“…Since MLF is one of the main energy sources during winemaking, the inhibition of the bacterial growth can be a consequence of the MLF inhibition. Rizk et al (2016) also showed that the same pairing (S. cerevisiae Uvaferm BDX/O. oeni Vitilactic F) maintained the MLF inhibition in Cabernet Sauvignon and Syrah wines.…”
Section: Introductionmentioning
confidence: 79%
“…This method was implemented and fully described by Rizk et al (2016). It consisted of preparing a cell-free enzymatic extract containing the malolactic enzyme of O. oeni Vitilactic F. The enzymatic extract was recovered in 2 mL of a buffer (0.1 M of citrate buffer pH 3.5, phosphate buffer pH 6 or phosphate buffer pH 6.7).…”
Section: In Vitro Evaluation Of the Peptidic Fractions Effect On The mentioning
confidence: 99%
See 2 more Smart Citations
“…Later, it was found that this fraction reached its highest concentration at late stages of the stationary phase and that it was able to directly inhibit the malolactic enzyme activity in vitro (Rizk et al., ). These results suggest that the peptide enter in the bacterial cytoplasm, by mechanisms yet to be identified, in order to reach the malolactic enzyme.…”
Section: Alternative To So2 For the Microbiological Stabilization Of mentioning
confidence: 99%